Hadhramaut and its diaspora : Yemeni politics, identity and migration - Brehony, Noel (Library of modern Middle East studies, 2017)
"Hadhramis have migrated for centuries in large numbers, establishing a diaspora that extends around the Indian Ocean, Saudi Arabia and the other Gulf States. This migration has deeply affected the host countries as well as Hadhramaut itself. Yet the region has not been able to use its population size, capabilities or resources to wield significant political influence in successive Yemeni regimes. This book examines the people of the Hadhrami diaspora, who travelled as religious scholars, traders, labourers and soldiers, to understand their enduring influence and identity. In doing so, the book explores key aspects of their history, including the impact of Yemeni nationalist movements, the significance of land reforms, the importance of social and tribal origins and how the Hadhrami resisted European domination as a Muslim community. Although a distinctive part of geographical Yemen, Hadhramaut was not regarded as a Yemeni political entity until the twentieth century. This research asks if the recent turmoil in Yemen following the Arab Spring, the growth of Al-Qa'ida and ISIS, and war involving a coalition led by Saudi Arabia, will produce even greater instability in the region or perhaps lead to a united Yemen, a restored South Yemen or even to Hadhramaut as an independent state. Hadhramaut and its Diaspora also explores what role the diaspora can play in shaping the future of their homeland."--